The impact of the two-year COVID-19 pandemic on hospital admission and readmissions of children and adolescents because of mental health problems - Raffagnato, Alessia; Miscioscia, Marina; Bruni, Gaia; Del Col, Lara; Traverso, Annalisa; Ferrarese, Martina; Ancora, Caterina; Zanato, Silvia; Gatta, Michela (Frontiers in Public Health, 2023)
Purpose This study aimed to investigate the specific risk factors and psycho-social and clinical features of hospitalized neuropsychiatric patients during the COVID pandemic and to analyze the hospital readmission phenomenon, which, according to recent studies, increased in frequency during the first pandemic period. Patients and methods This observational retrospective cohort study examined 375 patients aged between 0 and 17 years who were hospitalized between 1 February 2018 and 31 March 2022 due to neuropsychiatric issues. The majority of the patients were girls: there were 265 girls compared to 110 boys (M = 13.9 years; SD 2.30 years). The total sample was divided into two groups: the pre-COVID-19 group (160 inpatients hospitalized between February 2018 and February 2020) and the COVID-19 group (215 inpatients hospitalized between March 2020 and March 2022). To explore the readmission phenomenon (second aim), we selected from the two groups of patients with at least one hospital readmission within 365 days after the first discharge. Multiple variables (sociodemographic, clinical, psychological, and related to hospitalization) were collected for each patient by reviewing their medical records. Results The risk factors for mental health disorders were similar between the two groups, except for the significantly increased use of electronic devices in the COVID-19 group, increasing from 8.8% in the pre-COVID-19 group to 29.2% in the COVID-19 group. Patients suffering from eating disorders increased from 11.3% in the pre-COVID-19 group to 23.8% in the COVID-19 group. Hospital readmissions nearly increased from 16.7% in the 2-year pre-COVID-19 period to 26.2% in the 2-year COVID-19 period. A total of 75% of patients hospitalized three or more times in the last 2 years and 85.7% of the so-called “revolving door” patients (with relapse within 3 months after discharge) were identified in the COVID-19 group. However, the comparison between the two groups of patients readmitted before and during the COVID-19 pandemic did not show any differences in terms of sociodemographic and clinical characteristics. Conclusion In conclusion, there was a significant increase in hospital readmissions, but these results suggest the need for better coordination between hospital and territorial services in managing the complexity of mental health problems related to situations arising from the COVID-19 pandemic and the necessity to implement prevention strategies and services.